IMPLEMENTATION OF CHARACTER EDUCATION STRENGTHENING PROGRAM AT SDN 008 SAMARINDA - Nur Agus Salim (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
This study aims to determine how to strengthen character education at SDN 008 Samarinda. The data analysis technique for closed questionnaire data and interviews used descriptive qualitative analysis. The implementation of character education at SDN 008 Samarinda runs by the school's vision, mission and goals. There are eight-character values developed at SDN 008 Samarinda, namely religious, honest, tolerant, disciplined, democratic, national spirit, love for the homeland, and responsibility. Character education can be implemented through the learning process, school rules, and extracurriculars. The method used in implementing character education at SDN 008 Samarinda is by lecturing or giving examples directly because with this method, students can better understand what the teacher is saying.